Restoration and Development of Indigo-Dyed Cotton in Ban Na Muang Textile Handicraft Group, Phitsanulok via community participation - Pantung, Pornchai (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2021)
This study has objectives as follows: 1) to develop knowledge about indigo-dyed cotton to Ban Na Muang Textile Handicraft Group and 2) to develop, publicize, and evaluate the satisfaction of the indigo-dyed cotton product. The study procedures are 1) create knowledge about indigo-dyed cotton to Ban Na Muang Textile Handicraft Group, 2) design patterns of indigo-dyed cotton and develop products, 3) marketing promotion and product standards development, and 4) publicize the learning center of Ban Na Muang indigo-dyed cotton. Samples were selected by purposive sampling among Ban Na Muang Textile Handicraft Group. The total number of samples is 40. Tools in the study was interview forms, observation forms, and consumer satisfaction questionnaires towards products which used to collect data from 500 respondents. Then, data was analyzed for percentage, mean, and S.D. From the study, the knowledge development process from the practical transfer about indigo-dyed cotton with the community participation of Ban Na Muang Textile Handicraft Group is changed and new patterns of indigo-dyed cotton. New products are shawls, indigo-dyed t-shirts, shirt design, tie-dye technique, lamps, and chairs. Products are certified by OTOP and publicized via Facebook and NBT TV. Customer satisfaction towards products in terms of the pattern has the average score of 4.00 (high), the utility has the average score of 4.02 (high), the shape has the average score of 4.10 (high), and material and production process have the average score of 3.93 (high).